Strengths and limitations of small and medium-sized maize seed companies in Latin America - Silva Hinojosa, Arturo; Boddupalli, P.M.; Davis, Nicholas (International Maize and Wheat Improvement Center, 2022)
Towards the end of 2010, the International Maize and Wheat Improvement Center (CIMMYT) promoted the formation of a public-private partnership in Mexico that linked the main maize research and improvement centers (such as CIMMYT, INIFAP, Chapingo Autonomous University, among others), with the private seed production and marketing sector. Dubbed the Maize Seed Consortium, one of its main objectives was to evaluate, develop and/or deploy new high-yielding maize hybrids for distribution to maize grain producers, and at the same time contribute to the strengthening and diversification of the seed sector in Mexico. However, despite having had access to improved germplasm from research institutions such as CIMMYT, and having adopted new competitive hybrids, significant scope still remains to improve rainfed maize yields in Mexico. This document seeks to describe the strengths and limitations of Latin American small- and medium-sized seed enterprises (“seed SMEs”), with a particular focus on Mexican companies that colaborated with CIMMYT between 2011 and 2021, by studying a representative sample consisting of 10 companies whose marketing data and product portfolio were analyzed in depth. The study serves as the basis for recommending actionsthat can further strengthen the Latin American seed sector, and interventions that are required to overcome its present weaknesses. As appropriate, these findings and recommendations can be extrapolated and applied to other Latin American SMEs such as those in Central America, Ecuador, Bolivia, Venezuela, and Colombia, for which information is also included.